OP0060 SAFETY PROFILE OF ETANERCEPT IN LONG-TERM USE IN PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS (JIA). (June 2019) - Klotsche, Jens; Klein, Ariane; Niewerth, Martina; Ganser, Gerd; Aries, Peer; Walther, Marisa; Haas, Peter; Keyßer, Gernot; Horneff, Gerd; Minden, Kirsten
Abstract : Background: Etanercept is the most frequently used biologic drug in patients with JIA. Children and adolescents with JIA are treated with etanercept often over long periods of time, sometimes even into adulthood. The knowledge about its long-term safety, especially with regard to the occurrence of new-onset immune-mediated diseases and malignancies, is still limited. Objectives: To investigate the exposure-adjusted rates of adverse events (AE) and serious AE (SAE) in patients with JIA with long-term use of etanercept. Methods: Patients with JIA who were enrolled in the German biologic register BiKeR and were born before 30.05.2000 (at least 18 years of age at this date) were considered for this analysis. The follow-up register JuMBO ensures the long-term follow-up into adulthood. An AE or SAE was attributed to etanercept when the treatment was either ongoing or terminated in less than 3 month prior to the event. The incidence of malignancies was estimated in patients who were ever exposed to etanercept with at least one dose. Results: Of 4546 patients who were currently enrolled in BiKeR a total of 2584 JIA patients were eligible for the JuMBO register (>18 years). Among those, 1765 (68%) were ever exposed to etanercept and observed for a mean of 6.8±4.9 years (including 1101 into adulthood). The majority of them had polyarthritis (35%), followed by enthesitis-related arthritis (20%) and extended oligoarthritis (17%). The patients were exposed to etanercept for a total of 4.2 years (mean, 6, 726 exposure years, EY); 518 patients were continuously treated with etanercept for at least 5 years (4, 534 EY). In total, 124 autoimmune events (1.84/100EY) and 7 other immune disorders (0.10/100EY) were reported in 102 (5.8%) and 7 (0.4%) patients with onset on average 10.2 years after JIA onset, and 6.8 years after start with etanercept, respectively. The number of selected immune-mediated events and the exposure-adjusted rates are given in the table. In addition, 11 malignancies (0.10 events/100 person-years) were reported in patients ever exposed to etanercept. Among those (mean age at onset 20.3 years), 4 malignancies were reported in childhood and 7 in young adulthood. Three patients were also exposed to other biologics before the incidence of malignancy. The malignancies occurred on average 12.1 years after JIA onset, 10.4 years after start with a first DMARD and 7.5 years after first exposure to etanercept. Conclusion: This is the first long-term large safety study in prospectively followed JIA patients with focus on new-onset immune-mediated diseases and malignancies in etanercept. The study also highlights that it is important to prospectively collect data on adverse events under treatment with biologics in JIA, in particular with respect to the risk of malignancies in young adulthood. Disclosure of Interests: Jens Klotsche: None declared, Ariane Klein: None declared, Martina Niewerth: None declared, Gerd Ganser: None declared, Peer Aries: None declared, Marisa Walther: None declared, Peter Haas Grant/research support from: Pfizer, Gernot Keyßer: None declared, Gerd Horneff: None declared, Kirsten Minden Consultant for: AbbVie